STUDY OF TECTONIC STRAIN ON OPTIONS ELASTIC AND ACOUSTIC ANISOTROPY FERROUS QUARTZITES KRIVOY ROG ULTRADEEP WELLS ACCORDING ON THE DATA OF MATHEMATICAL MODELING - Prodayvoda, G.; Bezrodniy, D.; Bezrodna, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Influence of plastic, elastic-plastic and brittle deformations on the acoustic and elastic parameters of anisotropy is considered on the models of "ferrous quartzite", which are characterized with different systems of orientation of mikrocraccks and minerals. It is set that with growth of level of deformation transformations parameters of anisotropy change: the parameters of integral and differential coefficients of acoustic anisotropy grow thus in a different measure which can serve as a reliable indicator at determination of mark of tectonic facieses